Implementasi Kegiatan IMTAQ dalam Meng-Upgrade Skill Spiritual Siswa di SMA Muhammadiyah Kota Bima - Yani; Reka Purnama; Nasaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Rapid technological developments are one of the reasons for the shift in spiritual values. Therefore, organizing Imtaq (religious and taqwa) activities is an alternative way to develop students' spiritual skills in schools. This study aims to analyze the implementation of Imtaq activities in upgrading students' spiritual skills at Muhammadiyah Senior High School in Bima City. The research method used was qualitative with a descriptive approach. The results indicate that Imtaq activities can develop students' spiritual skills at Muhammadiyah Senior High School in Bima City, although not all students are successful. These activities are carried out in stages, starting with the recitation of the Qur'an, Surah Al-Kahf, followed by reading a verse and its translation, followed by a lecture, then a prayer, and concluding with a prayer. These activities have supporting and inhibiting factors, including factors from the school environment, family, and community, and even factors within the students themselves. Implementing Imtaq activities in schools can optimize the development of students' spiritual skills.